Phase-specific Fe0/H₂O₂ Fenton-like treatment enhances humification and suppresses antibiotic resistance gene rebound during sewage sludge composting - Imtiaz Ahmed; Dong Zhang; Muhammad Umar Farooq; Chengyu Li; Chenxuan Yu; Jiawang He; Zeshan Sheikh; Xiaohu Dai (Chemical Engineering Journal, 2026)

Assessment of growth and physiological effects of dietary Arthrospira platensis in broiler chickens - Zain Ul Abideen; Muhammad Zeshan Haider; Muhammad Kashif Zaman; Muhammad Farooq; Amin F. Majdalawieh; Imad A. Abu-Yousef; Tahira Ruby; Aleem Ahmed Khan (Livestock Science, 2026)

CRISPR-based gene editing for antimicrobial resistance control in human medicine - Abdullah Afzal Alvi; Muzzamil Hussain; Sadia Noureen; Zahid Abbas Malik; Sidra Zahoor; Areej Jamil; Muhammad Ali Mohsin; Asad Azeem; Haseeb Javaid; Zeshan Hassan (Archives of Microbiology, 2026)

Influence of thermal pretreatment on characteristic and anaerobic digestion of Sunflower meal - Asad Ayub Rajput; Zeshan; Muhammad Raheel Bawani; Saleem Raza Chalgri (Bioresource Technology Reports, 2026)

Integrated BIM-GIS and finite element-based framework for building planning and design - Aaqib Najeeb; Zili Zhang; Muhammad Arsalan Khan; Kong Fah Tee; Taimoor Shehzad; Abid Ali Shah; Zeshan Alam (Innovative Infrastructure Solutions, 2026)

Unraveling the phototransformation of 2,4,6-tribromophenol: Aqueous mechanisms involving ·OH and the emergence of hydroxylated PBDEs - Junling Ma; Muhammad Zeshan; Rong Cao; Hong-bin Xie; Ningbo Geng; Haijun Zhang; Yuan Gao; Lidong Wu; Jiping Chen (Water Research, 2026)

Microplastics exacerbate antibiotic resistance by regulating microbial and functional gene dynamics in sludge and food waste composting - Imtiaz Ahmed; Dong Zhang; Muhammad Umar Farooq; Zeshan Sheikh; Xiaohu Dai (Water Research, 2026)

Synergistic effects of biochar and PGPR in enhancing the efficacy of biological control agents against Ganoderma boninense in oil palm (Elaeis guineensis L.): a critical review - Qudrat Ullah; Muhammad Zeshan; Waqas Haider; Muhammad Waqar; Zaki ul Zaman Asam; Muhammad Zubair; Mujahid Farid (Archives of Microbiology, 2026)

Technological frontiers and optimization in solar power towers: innovations in thermal energy storage, receivers, and heliostat systems - Zeshan Aslam; Syed Ihtsham Ul Haq Gilani; Taib Iskandar Mohamad; Masdi Muhammad; Kehinde Temitope Alao (Clean Technologies and Environmental Policy, 2025)

An Inclusive Approach to Disaster Risk Reduction in Water-Related Hazards for the Mining Industry: Prioritizing the Multi-Dimensional Risk Framework for Achieving Sustainable Development - Aboubakar Siddique; Zhuoying Tan; Jiang Li; Asaad Algarni; Irshad Ali Zardari; Muhammad Zeshan; Saddam Hussain Khurram; Dhanesh Kumar (Mine Water and the Environment, 2025)

Incorporating dynamic crop area in hydrological model to address interannual variability in water withdrawal and implication of sustainable water management - Muhammad Umer; Naota Hanasaki; Saritha Padiyedath Gopalan; Zeshan Ali; Taikan Oki (Journal of Hydrology, 2025)

Prediction of water status during freeze drying with genetic and whale algorithms of machine learning - Shoaib Younas; Muhammad Ahmad; Ukasha Arqam; Muhammad Sajid Manzoor; Xin Wang; Weijie Li; Caiyun Liu; Zeshan Ali; Muhammad Azeem Sabir; Muhammad Imran (International Journal of Refrigeration, 2025)

Remarkable energy storage performance in lead-free tungsten bronze ferroelectrics for high temperature applications - Muhammad Fahad Riaz; Fayaz Hussain; Ali Dad Chandio; Zeshan Javed; Wenfeng Yue; Zhenhao Fan; Yuxiao Du; Bingsen Wang; Mohammad Abu Abdeen; Gulmurza Abdurakhmanov; Adil Alshoaibi; Yasemin Tabak; et al. (Chemical Engineering Journal, 2025)

Unveiling sources of organophosphate esters in marine environments utilizing multi-factor multi-modal high-dimensional clustering algorithm - Nan Hu; Xing Liu; Muhammad Zeshan; Jian Qu; Haijun Zhang; Yuan Gao; Ziwei Yao; Jiping Chen (Water Research, 2025)

Circular RNAs: Diversity, formation, functions, and identification mechanism with a focus on endogenous circular RNAs - Muhammad Umer; Naureen Anwar; Mustansar Mubeen; Yasir Iftikhar; Manoj Kumar Solanki; Muhammad Ahmad Zeshan; Khalid M. Alsyaad; Yun Li; Pingwu Liu (Physiological and Molecular Plant Pathology, 2025)

Advancing fungal phylogenetics: integrating modern sequencing, dark taxa discovery, and machine learning - Syed Atif Hasan Naqvi; Aqleem Abbas; Ammarah Hasnain; Zeshan Bilal; Fahad Hakim; Muhammad Shabbir; Ahsan Amin; Muhammad Umer Iqbal (Archives of Microbiology, 2025)

Turn-On-Fluorescence Sensor and Solid Sensory Chip for Cyanide Detection - Muhammad Zahid; Nadeem Raza; Samuel Bonne; Mostafa E. Salem; Negin G. Niksirat; Muhammad Zeshan; Muhammad Rafiq; Jian Zhang; Muhammad Saleem (Journal of Fluorescence, 2025)

Association mapping of leaf rust disease resistance and yield related traits in bread wheat using a high density 90K SNP array - Muhammad Rauf Shah; Muhammad Ali Sher; Salma Bashir; Muhammad Zeshan Zafer; Douglas Law; Sania Begum; Nasr Ullah Khan; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Daniel K. Y. Tan; Muhammad Yasin (Journal of Plant Diseases and Protection, 2025)

Retraction notice to “Mycorrhizosphere bacteria inhibit greenhouse gas emissions from microplastics contaminated soil by regulating soil enzyme activities and microbial community structure” [J. Environ. Manag. 356 (2024) 120673] - Zeeshan Khan; Tariq Shah; Ghulam Haider; Fazal Adnan; Zeshan Sheikh; Mohamed A. El-Sheikh; Muhammad Faraz Bhatti; Parvaiz Ahmad (Journal of Environmental Management, 2025)

Advancements in metal selenide nanocomposites for efficient photocatalytic water splitting applications - Zeshan Ali Sandhu; Soha Ghaffar; Muhammad Asam Raza; Noor ul Huda; Sufyan Ashraf; Umair Talat; Areej Chauhdary; Hamza Gulzarab; Abdullah G. Al-Sehemi (Fuel, 2025)

Socio-economic benefits and policy implications of generating sustainable energy from municipal solid waste in Pakistan - Waqas Ahmad; Muhammad Hassan; Shah Fahad Bin Masud; Muhammad Saad Amjad; Fatin Samara; Zeshan; Mustafa Anwar; Muhammad Zeeshan Rafique; Tahir Nawaz (Energy and Climate Change, 2024)

Sustainability and photocatalytic performance of MOFs: Synthesis strategies and structural insights - Zeshan Ali Sandhu; Umme Farwa; Muhammad Danish; Muhammad Asam Raza; Aqib Talib; Hifza Amjad; Rukhmah Riaz; Abdullah G. Al-Sehemi (Journal of Cleaner Production, 2024)

Yeast-based solutions in controlling plant pathogens - Amjad Ali; Fatih Ölmez; Muhammad Ahmad Zeshan; Mustansar Mubeen; Yasir Iftikhar; Ashara Sajid; Muhammad Abid; Ajay Kumar; Praveen Kumar Divvela; Manoj Kumar Solanki (Biocatalysis and Agricultural Biotechnology, 2024)

Effect of hydraulic retention time on wastewater treatment and microalgal growth at low light intensity - Ramsha Malik; Sahar Saleem; Muhammad Basharat; Muhammad Faraz Bhatti; Zeshan Sheikh (Algal Research, 2024)

Hollow CoP/carbon as an efficient catalyst for the peroxymonosulfate activation derived from phytic acid assisted metal-organic framework - Muhammad Abdul Nasir Khan; Prosper Kwame Klu; Chengming Xiao; Junwen Qi; Tayyaba Noor; Zeshan Sheikh; Kaleemullah Kalwar; Jiansheng Li (Chemosphere, 2024)

RETRACTED: Mycorrhizosphere bacteria inhibit greenhouse gas emissions from microplastics contaminated soil by regulating soil enzyme activities and microbial community structure - Zeeshan Khan; Tariq Shah; Ghulam Haider; Fazal Adnan; Zeshan Sheikh; Mohamed A. El-Sheikh; Muhammad Faraz Bhatti; Parvaiz Ahmad (Journal of Environmental Management, 2024)

Genetics aspect of vitamin C (Ascorbic Acid) biosynthesis and signaling pathways in fruits and vegetables crops - Adnan Sami; Shiming Han; Muhammad Zeshan Haider; Rameen Khizar; Qurban Ali; Muhammad Shafiq; Javaria Tabassum; Muhammad Nouman Khalid; Muhammad Arshad Javed; Mateen Sajid; Muhammad Aamir Manzoor; Irfan Ali Sabir (Functional & Integrative Genomics, 2024)

Performance comparison of a photosynthetic and mechanically aerated microbial fuel cell for wastewater treatment and bioenergy generation using different anolytes - Zia Ullah; Zeshan Sheikh; Waqas Qamar Zaman; Muhammad Zeeshan; Waheed Miran; Jiansheng Li; Muhammad Abdul Nasir Khan; Sahar Saleem; Shanza Shabbir (Journal of Water Process Engineering, 2023)

Hydrological response under CMIP6 climate projection in Astore River Basin, Pakistan - Zeshan Ali; Mudassar Iqbal; Ihsan Ullah Khan; Muhammad Umer Masood; Muhammad Umer; Muhammad Usama Khan Lodhi; Muhammad Atiq Ur Rehman Tariq (Journal of Mountain Science, 2023)
Climate change strongly influences the available water resources in a watershed due to direct linkage of atmospheric driving forces and changes in watershed hydrological processes. Understanding how these climatic changes affect watershed hydrology is essential for human society and environmental processes. Coupled Model Intercomparison Project phase 6 (CMIP6) dataset of three GCM’s (BCC-CSM2-MR, INM-CM5-0, and MPI-ESM1-2-HR) with resolution of 100 km has been analyzed to examine the projected changes in temperature and precipitation over the Astore catchment during 2020–2070. Bias correction method was used to reduce errors. In this study, statistical significance of trends was performed by using the Man- Kendall test. Sen’s estimator determined the magnitude of the trend on both seasonal and annual scales at Rama Rattu and Astore stations. MPI-ESM1-2-HR showed better results with coefficient of determination (COD) ranging from 0.70–0.74 for precipitation and 0.90–0.92 for maximum and minimum temperature at Astore, Rama, and Rattu followed by INM-CM5-0 and BCC-CSM2-MR. University of British Columbia Watershed model was used to attain the future hydrological series and to analyze the hydrological response of Astore River Basin to climate change. Results revealed that by the end of the 2070s, average annual precipitation is projected to increase up to 26.55% under the SSP1–2.6, 6.91% under SSP2–4.5, and decrease up to 21.62% under the SSP5–8.5. Precipitation also showed considerable variability during summer and winter. The projected temperature showed an increasing trend that may cause melting of glaciers. The projected increase in temperature ranges from - 0.66°C to 0.50°C, 0.9°C to 1.5°C and 1.18°C to 2°C under the scenarios of SSP1–2.6, SSP2–4.5 and SSP5–8.5, respectively. Simulated streamflows presented a slight increase by all scenarios. Maximum streamflow was generated under SSP5–8.5 followed by SSP2–4.5 and SSP1–2.6. The snowmelt and groundwater contributions to streamflow have decreased whereas rainfall and glacier melt components have increased on the other hand. The projected streamflows (2020–2070) compared to the control period (1990–2014) showed a reduction of 3%–11%, 2%–9%, and 1%–7% by SSP1–2.6, SSP2–4.5, and SSP5–8.5, respectively. The results revealed detailed insights into the performance of three GCMs, which can serve as a blueprint for regional policymaking and be expanded upon to establish adaption measures.

Increased health risk assessment in different vegetables grown under untreated sewerage irrigation regime due to higher heavy metals accumulation - Zeshan Hassan; Ammara Hassan; Muhaiman Riaz; Azhar Abbas Khan; Sami Ul-Allah; Umbreen Shehzad; Muhammad Khurshid; Ali Bakhsh; Jawad Munawar Shah; Zahid Manzoor (Environmental Science and Pollution Research, 2023)

Antibiotics induced changes in nitrogen metabolism and antioxidative enzymes in mung bean (Vigna radiata) - Marium Fiaz; Iftikhar Ahmed; Sumara Masood Ul Hassan; Adnan Khan Niazi; Muhammad Fahim Khokhar; Zeshan; Muhammad Ansar Farooq; Muhammad Arshad (Science of The Total Environment, 2023)

Moringa oleifera leaf extract mediated green synthesis of silver nanoparticles and their antibacterial effect against selected gram-negative strains - Mehwish Younas; Muhammad Hidayat Rasool; Mohsin Khurshid; Amjad Khan; Muhammad Zeshan Nawaz; Ijaz Ahmad; Muhammad Nazim Lakhan (Biochemical Systematics and Ecology, 2023)

Elucidating molecular characterization of chlorpyrifos and profenofos degrading distinct bacterial strains for enhancing seed germination potential of Gossypium arboreum L - Najeeba Paree Paker; Shehzad Mehmood; Muhammad Tariq Javed; Christos A. Damalas; Fazal ur Rehman; Hassan Javed Chaudhary; Muhammad Zeshan Munir; Mahrukh Malik (Environmental Science and Pollution Research, 2023)

Deciphering the Role of Plant-Derived Smoke Solution in Ameliorating Saline Stress and Improving Physiological, Biochemical, and Growth Responses of Wheat - Sumera Shabir; Noshin Ilyas; Saira Asif; Muhammad Iqbal; Sidra Kanwal; Zeshan Ali (Journal of Plant Growth Regulation, 2022)

Lethal and sublethal effects of flonicamid (50 WG) and spirotetramat (240 SC) on Bemisia tabaci (Homoptera: Aleyrodidae): an age-stage two sex life table study - Aqsa Abbas; Javaid Iqbal; Ali Zeshan; Qurban Ali; Imran Nadeem; Humaira Malik; Tamsila Nazir; Muhammad Faheem Akhter; Bilal Bin Iqbal (Phytoparasitica, 2022)

Temporal variation in leachate composition of a newly constructed landfill site in Lahore in context to environmental pollution and risks - Mahsoon Ashraf; Muhammad Zeshan; Sadia Hafeez; Rahib Hussain; Abdul Qadir; Muzaffar Majid; Farman Ahmad; Sajid Rashid Ahmad (Environmental Science and Pollution Research, 2022)

Assessing the potential of partial root zone drying and mulching for improving the productivity of cotton under arid climate - Rashid Iqbal; Muhammad Habib-ur-Rahman; Muhammad Aown Sammar Raza; Muhammad Waqas; Rao Muhammad Ikram; Muhammad Zeshan Ahmed; Monika Toleikiene; Muhammad Ayaz; Farhan Mustafa; Salman Ahmad; Muhammad Usman Aslam; Muhammad Mohsin Waqas; et al. (Environmental Science and Pollution Research, 2021)
Water scarcity constrains global cotton production. However, partial root-zone drying (PRD) and mulching can be used as good techniques to save water and enhance crop production, especially in arid regions. This study aimed to evaluate the effects of mulching for water conservation in an arid environment under PRD and to further assess the osmotic adjustment and enzymatic activities for sustainable cotton production. The study was carried out for 2 years in field conditions using mulches (NM = no mulch, BPM = black plastic mulch at 32 kg ha -1 , WSM = wheat straw mulch at 3 tons ha -1 , CSM = cotton sticks mulch at 10 tons ha -1 ) and two irrigation levels (FI = full irrigation and PRD (50% less water than FI). High seed cotton yield (SCY) achieved in FI+WSM (4457 and 4248 kg ha -1 in 2017 and 2018, respectively) and even in PRD+WSM followed by BPM>CSM>NM under FI and PRD for both years. The higher SCY and traits observed in FI+WSM and PRD+WSM compared with the others were attributed to the improved water use efficiency and gaseous exchange traits, increased hormone production (ABA), osmolyte accumulation, and enhanced antioxidants to scavenge the excess reactive oxygen. Furthermore, better cotton quality traits were also observed under WSM either with FI or PRD irrigation regimes. Mulches applications found effective to control the weeds in the order as BPM>WSM>CSM. In general, PRD can be used as an effective stratagem to save moisture along with WSM, which ultimately can improve cotton yield in the water-scarce regions under arid climatic regions. It may prove as a good adaptation strategy under current and future water shortage scenarios of climate change.

Metal accumulation potential, human health risks, and yield attributes of hundred bread wheat genotypes on irrigation with municipal and remediated wastewater - Said Akbar; Zeshan Ali; Sadam Hussain; Ashiq Mohammad; Yousaf Riaz; Adnan Shakeel; Ijaz Ahmad; Maria Mussarat; Riffat Naseem Malik; Kiran Yasmin Khan; Muhammad Sohail; Umar Masood Quraishi (Environmental Science and Pollution Research, 2021)

Double-hit scenario of Covid-19 and global value chains - Muhammad Zeshan (Environment, Development and Sustainability, 2021)

Influence of Pseudomonas japonica and organic amendments on the growth and metal tolerance of Celosia argentea L. - Ameena Iqbal; Muhammad Umair Mushtaq; Aqib Hassan Ali Khan; Ismat Nawaz; Sohail Yousaf; Zeshan; Mazhar Iqbal (Environmental Science and Pollution Research, 2020)

Photocatalytic Performance of Zinc Ferrite Magnetic Nanostructures for Efficient Eriochrome Black-T Degradation from the Aqueous Environment under Unfiltered Sunlight - Ikramullah; Nisar Ali; Farman Ali; Zeshan Ali Sheikh; Muhammad Bilal; Iftikhar Ahmad (Water, Air, & Soil Pollution, 2020)

Comparative study of the genetic basis of nitrogen use efficiency in wild and cultivated barley - Jawad Munawar Shah; Sidra tul Muntaha; Essa Ali; Azhar Abbas Khan; Syed Hassan Raza Zaidi; Ahmad Naeem Shahzad; Zeshan Hassan; Ahmad Nawaz; Muhammad Rashid; Syed Asad Hussain Bukhari (Physiology and Molecular Biology of Plants, 2019)

Carbon footprint accounts of Pakistan: an input-output life cycle assessment model - Muhammad Zeshan (Environmental Science and Pollution Research, 2019)

Evaluation of Green Waste and Popular Twigs Biochar Produced at Low and High Pyrolytic Temperature for Efficient Removal of Metals from Water - Zeshan Aslam; Muhammad Khalid; Muhammad Naveed; Muhammad Shahid; Muhammad Aon (Water, Air, & Soil Pollution, 2017)

Assessment of heavy metals and metalloids in tissues of two frog species: Rana tigrina and Euphlyctis cyanophlyctis from industrial city Sialkot, Pakistan - Irfan Zia Qureshi; Zeshan Kashif; Muhammad Zaffar Hashmi; Xiaomei Su; Riffat Naseem Malik; Kalim Ullah; Jinxing Hu; Muhammad Dawood (Environmental Science and Pollution Research, 2015)

Energy, environment and growth nexus in South Asia - Muhammad Zeshan; Vaqar Ahmed (Environment, Development and Sustainability, 2013)

Mitigation of ruminant methane production: current strategies, constraints and future options - Muhammad Farooq Iqbal; Yan-Fen Cheng; Wei-Yun Zhu; Basit Zeshan (World Journal of Microbiology and Biotechnology, 2008)